Endocrine disruptors in the environment - Khetan, Sushil K. (John Wiley & Sons, Inc., 2014)
For most of the last decade, the science of endocrine disruption has evolved with more definitive evidence of its damaging potential to health and the environment. This book lists the major environmental chemicals of concern and their mechanism of endocrine disruption including remedial measures for them. Divided into three parts, it begins with an overview of the endocrine system and endocrine disruptors. It then goes on to cover hormone-signaling mechanisms, followed by various broad classes of putative endocrine disruptors, before introducing readers to environmental epigenetic modifications. Part two of the book focuses on removal processes of various EDCs by biotic and abiotic transformation/degradation. The last section consists of four chapters embracing themes on finding solutions to environmental EDCs. -- Edited summary from book.
Keywords: Endocrine disrupting chemicals -- Environmental aspects.; Endocrine disrupting chemicals -- Toxicity testing.; Endocrine toxicology.; Pollution.; elektronické knihy; electronic books